Some honest talk about Non-Indigenous Education - Derek Rasmussen (Canadian Centre for Policy Alternatives (CCPA), 2011)
Euro-Canadians try and play it both ways when we use the word “education.” On the one hand we claim open-mindedness by asserting platitudes like ‘all societies have education’ — including Indigenous societies. And on the other hand, we then frequently refer to Indigenous people as “uneducated”--casually denigrating them because they weren’t admitted into or didn’t graduate out of the deliberately narrow funnel we've invented: European institutional education. This can be termed the “Restaurant Theory of Education”, wherein we think of the relationship between Education (scarce) and cultural trans-mission (wide) as being like the relationship between restaurants and food. Restaurants can be found in most Euro-Canadian neighborhoods—as can schools—butt we don't believe that without restaurants we would starve. If we come across a society without schools, then we assume that there has to be some sort of Education system hidden in the social structure somewhere and we just have to suss it out. Yet if we don’t see restaurants in another civilization we don’t immediately assume that they must have a restaurant system hidden in their food relations somewhere.